Students Strategies In English Vocabulary Learning - Ningtyas, Yunia Dwi; Octavia, Calista Dyah; Fuadillah, Rizka Anis (Prosiding University Research Colloquium, 2021)
The vocabulary is an important elemen in English mastery. Limited vocabulary will prevent student from communitation in English. The importance of vocabulary in language learning is also illustrated by Mr. Wilkins (thorn bury, 2003:13), stating that “without vocabbbulary, nothing can be stressed; without vocabulary, nothing can be bulletproof ‘. Futher he posses that by studying a vocabulary one will be able radiply improving language ability. There fore need ti implement appropriate learning strategies. There are several learning strategies such as the TPR method, learning by song, learning by plan and so on. Vocabulary is really important to learn. Without grammar, little can be conveyed, but without vocabulary nothing can be conveyed.